It's about time: catching method up to meaning - the usefulness of narrative inquiry in public administration research - Ospina, Sonia M.; Dodge, Jennifer (2005)
As a form of interpretive research, narrative inquiry contributes to the pursuit of high-quality public administration scholarship, along with other forms of explanatory research that have dominated the field. In this article we discuss the unique features of narrative inquiry, review how this research orientation has been used in public administration, and use our experience with a national, multimodal, multiyear research project on social-change leadership in the United States to identify and illustrate the contributions of narrative inquiry to address two key issues in the field: the concern with good research and the aspiration to cultivate a meaningful connection between researchers and practitioners in the field. - Reproduced.
Keywords: Research; Public administration